The Impact of Economics, Unemployment, and Minimum Wages on Poverty in Rembang - Nurul Hindayati (International Journal of Economics and Business Management, 2025)
Poverty remains a complex development challenge in many regions in Indonesia, including Rembang Regency. This study aims to analyze the influence of economic growth, the open unemployment rate (TPT), and the minimum wage on the poverty rate in Rembang Regency during the 2011–2020 period. Using secondary data from the Central Statistics Agency (BPS), this study applies a multiple linear regression method supported by classical assumption tests and statistical tests (t-test and F-test) using Eviews 10 software. The analysis results indicate that economic growth and the open unemployment rate do not significantly influence the poverty rate. On the other hand, the minimum wage is proven to have a negative and significant effect, indicating that minimum wage increases contribute to poverty reduction. These findings highlight the importance of equitable wage policies as a strategic instrument in poverty alleviation, while also suggesting that economic growth alone is not inclusive enough to reach the most vulnerable groups. The implications of this research can be used as considerations for local governments in designing more targeted and effective policy interventions.